ANALYSIS OF THE SHARIA ECONOMIC SYSTEM THROUGH THE RECONSTRUCTION OF THE NORMATIVE APPROACH BASIS AND HISTORICAL APPROACH OF SHARIA ACCOUNTING - Adriandi Kasim (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2025)
The discourse on Sharia economics begins with the concept of business economics that does not rely on usury practices. To achieve the ideal goal of Sharia economics, various supporting tools are needed, such as information systems, measuring tools, and accountability tools. One of these tools is Sharia accounting, based on the Quran and Hadith. However, many Sharia accounting practices have not fully implemented this foundation, causing Islamic accounting to lose its purity due to using more conventional accounting theories. This research aims to reconstruct the normative and historical foundations of Sharia accounting so that Islamic accounting can return to the guidelines of the Quran and Hadith. The methodology used in this research is a literature study or library research, one of the qualitative research methods. The data and materials used in this research come from various journals, books, and scriptures. The research results show that Islamic or Sharia accounting has been normatively ordered in the Quran. Accountability, justice, and truth must be followed in financial transactions and in preparing accounting reports. Historically, the Islamic accounting system was first applied in the time of the Prophet, with the obligation to record non-cash transactions to ensure that Muslims pay attention to recording their transactions. Sharia accounting continues to develop until the modern era.